Answer:
m=(-6,6)
Step-by-step explanation:
m^2 -36 = 0
Reorder the terms:
-36 + m^2 = 0
Solving for variable 'm'.
Add '36' to each side of the equation.
-36 + 36 + m^2 = 0 + 36
Combine like terms: -36 + 36 = 0
0 + m^2 = 0 + 36
m^2 = 0 + 36
Combine like terms: 0 + 36 = 36
m^2 = 36
Simplifying
m^2 = 36
Take the square root of each side:
√m^2=+/-√36
m=(+/-)6
m = {-6, 6}
Answer:
6
Step-by-step explanation:
24/4 is 6
Step-by-step explanation:
1) the domain is from -3 to 5 D [-3,5]
the range is from -5 to -2. R [-5,-2]
2)the domain is from -3 to 6 but not including 6 D [-3,6)
the range is from -5 but not including -5 to 2. R (-5,2]
-3x-2-6x=-4-<em>(-4x)</em>+12
-9x-2=-16x+12
7x=14
x=2.
You probably got confused with the italicized part.
B. F2. That is the deepest point in the decline.